Pelatihan Pembuatan Web Design Menggunakan HTML Dan CSS Di SMK Letris Indonesia 2 - Zainul Janariandana; Ahmad Faisal; Azmi Mubarok Astripat; Dewi Meidiyanti; Rizaludin Pahlevi Utomo; Rendyka Purnama; Rinna Rachmatika (CV. Multi Kreasi Media, 2023)
WEB DESIGN MAKING TRAINING USING HTML AND CSS AT SMK LETRIS 2 INDONESIA is a community service activity that aims to increase students' knowledge and understanding of creating a simple web. There are three main stages carried out in this service, including the planning stage, the implementation stage, and the evaluation stage. The results of the evaluation of the service activities that have been carried out are training on creating a simple web using VsCode, which can increase the knowledge and skills of Letris Indonesia 2 Vocational High School students. This training is carried out for one day by informatics engineering students at Pamulang University. The students directly practice on their respective lab computers or laptops. In the project session, they managed to create web programs individually.